2021
DOI: 10.3390/pharmaceutics13081314
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Odorant Receptor Responding to Flavor Compounds: Versatile Roles in Health and Disease

Abstract: Prompted by the ground-breaking discovery of the rodent odorant receptor (OR) gene family within the olfactory epithelium nearly 30 years ago, followed by that of OR genes in cells of the mammalian germ line, and potentiated by the identification of ORs throughout the body, our appreciation for ORs as general chemoreceptors responding to odorant compounds in the regulation of physiological or pathophysiological processes continues to expand. Ectopic ORs are now activated by a diversity of flavor compounds and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 165 publications
0
20
0
Order By: Relevance
“…Ectopic olfactory receptors have diverse functions in different organs and tissues [3,26,27]. Genital organs are exposed to odorants constantly; thus, ectopic olfactory receptors may regulate intracellular signaling pathways and related physiologic functions in these organs.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic olfactory receptors have diverse functions in different organs and tissues [3,26,27]. Genital organs are exposed to odorants constantly; thus, ectopic olfactory receptors may regulate intracellular signaling pathways and related physiologic functions in these organs.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this suggests that the aberrant expression of ORs might contribute to the cancer phenotype. In cancer cells, ORs act as chemoreceptors 52 . In comparison to healthy prostate tissue, prostate cancer shows a high tumor‐specific overexpression (i.e., more than 10‐fold) of OR51E1 and OR51E2 in two‐thirds of cases (Table 1) (Figure 1).…”
Section: Olfactory Receptorsmentioning
confidence: 99%
“…In cancer cells, ORs act as chemoreceptors. 52 In comparison to healthy prostate tissue, prostate cancer shows a high tumor-specific overexpression (i.e., more than 10-fold) of OR51E1 and OR51E2 in two-thirds of cases (Table 1) (Figure 1). The full spectrum of their ligands is still unknown, but deorphanization efforts showed that they can be activated by lactate, butyric acid, propionic acid, and other aliphatic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this suggests that the aberrant expression of ORs might contribute to the cancer phenotype. In cancer cells, ORs act as chemoreceptors 33 . In comparison to healthy prostate tissue, prostate cancer shows a high tumor-specific overexpression (i.e., more than 10fold) of OR51E1 and OR51E2 in two-third of cases 34 .…”
Section: Olfactory Receptorsmentioning
confidence: 99%